Dilema Pemberlakuan PP. No. 78 Tahun 2015 Tentang Pengupahan: Disparitas yang Kian Melebar - Mahesa, Rama; Sabar, Kurniawan (Universitas Brawijaya, 2019)
This study aims to examine the implementation of wage system in Indonesia based on Law No. 13/2003 and Government Regulation No. 78/2015 on labor conditions in Jabodetabek. The urgency of this study with regard to wage conditions in Indonesia that are still visible lags tend to widen the gap between workers and employers. It's a policy study by collecting secondary data and then analyzed into a conclusion and a recommendation. Descriptive qualitative study method used data collection techniques such as: documentation of literature study, discussion and grouping of research object data. The results of the study indicate that the new formula in determining the minimum wage and annual wage increase in Indonesia has been implemented based on PP no. 78 years 2015 which is based on inflation rate and economic growth. The new formula of minimum wage determination is opposed by the workers on the basis of not accommodating the fulfillment of life-worth needs and narrowing the rights of workers in democracy demanding a decent wage increase. Entrepreneurs view PP Wage has not accommodate the condition of UMKMÂ in the implementation of minimum wage that requires the structure of wages and wage scale (SUSU). The Regional Representative Council of the Republic of Indonesia (DPD RI), which is preparing the Wage System Bill, needs field data and facts related to the current wage condition. The important recommendations that can be considered by the DPD RI in the preparation of the Wage System Bill is the refinement of the legislative materials related to the evaluation of the components of Decent Living Needs (KHL) once in five years, the establishment of policies on the implementation of SUSU for UMKM and strengthening the supervisory function in the field of manpower especially in the regions.